2016
DOI: 10.3847/0004-6256/152/6/160
|View full text |Cite
|
Sign up to set email alerts
|

A 1.9 Earth Radius Rocky Planet and the Discovery of a Non-Transiting Planet in the Kepler-20 System*

Abstract: Kepler-20 is a solar-type star (V = 12.5) hosting a compact system of five transiting planets, all packed within the orbital distance of Mercury in our own solar system. A transition from rocky to gaseous planets with a planetary transition radius of ∼1.6 Å R has recently been proposed by several articles in the literature. Kepler-20b (R p ∼1.9 Å R ) has a size beyond this transition radius; however, previous mass measurements were not sufficiently precise to allow definite conclusions to be drawn regarding … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 63 publications
9
93
0
Order By: Relevance
“…We base the 5% metric on the range of uncertainties produced by LC estimates of P rot , used as priors in RV fits (e.g. López-Morales et al 2016;Buchhave et al 2016;Dai et al 2017).…”
Section: Investigation Of Simulated Rv Periodogramsmentioning
confidence: 99%
“…We base the 5% metric on the range of uncertainties produced by LC estimates of P rot , used as priors in RV fits (e.g. López-Morales et al 2016;Buchhave et al 2016;Dai et al 2017).…”
Section: Investigation Of Simulated Rv Periodogramsmentioning
confidence: 99%
“…Theoretically, given the small scatter in chemical abundances of stars in the solar neighborhood, rocky planet radii should not change much more than 2% due to differences in compositions (Grasset et al 2009), while WASP-47 e's radius is 7% larger than an Earth-like planet with the same mass. Moreover, observations of small, likely rocky planets near their host stars have shown that rocky exoplanets tend to have compositions consistent with that of the Earth (Dressing et al 2015;Buchhave et al 2016). It is unclear how a planet of this size, around a star of such high metallicity/iron content, could avoid accumulating any substantial amount of iron.…”
Section: Constraints On the Composition Of Wasp-47 Ementioning
confidence: 99%
“…Furthermore, RV measurements are being used to follow up planets discovered by the transit method to determine the bulk densities of transiting planets and to look for more non-transiting planets in the system (see for example Buchhave et al 2016).…”
Section: Introductionmentioning
confidence: 99%